PENGARUH FLUKTUASI HARGA, ETOS KERJA ISLAM DAN PENDAPATAN KELUARGA TERHADAP KESEJAHTERAAN PETANI KARET MUSLIM - N Aulya Putri Savira; Abdul Salam; Baiq Ismiati; Ahmad Yunadi (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to analyze the influence of price fluctuations, Islamic work ethic, and family income on the welfare of Muslim rubber farmers (case study of rubber farmers in Batumarta II). This study employs a quantitative method using questionnaires, involving 100 respondents selected using the Taro Yamane formula. The independent variables include price fluctuations (X1), Islamic work ethic (X2), family income (X3), while the dependent variable is welfare (Y). Data analysis is conducted using EViews 12 with reliability tests, classical assumptions, multiple linear regression, T-tests, F-tests, and R2 tests. The results show that the price fluctuation variable has a positive but insignificant effect on family well-being, while the variables of Islamic work ethos and family income have an effect on the welfare of Muslim rubber farmers in Batumarta II.